(3GdCYTGH aj cJGH (B: s (3GdGSJNOGeGJ GdWHjI(B-(3GdYdGLjI(B-(3GdJLejdjI(B-(3GdJUfjYjI (B/ s - (3YQehT, gGfjs; (3GdYeQj, ehabs ((3OeTb, ShQjG (B: s (3OGQ GdfaGFS ddWHGYI hGdfTQ hGdJhRjY,s, 2012)
(3GdcJGH ehShYI YTHjI JTed OQGSI eaUdI Yf GdGYTGH GdeNJdaIs
(3jJVef Odjd YGe, UaMI (B876-880s
(3jJVef GSeGA GdGYTGH HTcd gLGFjs
Keywords: (3GdGYTGHs